Kemandirian Pangan dengan Digital Marketing Hasil Urban Farming - Eviyanti, Ade; Abror, M.; Arifin, Saiful (Procedia of Social Sciences and Humanities, 2022)
Agricultural products developed by the community (members of the aisyiyah branch) through a partnership program with Pimpinan Aisyiyah Sidoarjo Region need a method to market so that it can be known by consumers. The use of yard land with the concept of urban farming produces several products including vegetables and fruits. The concept of urban farming is to utilize the land around the house or yard by growing organic vegetables polybag models, hydroponic systems, verticulture systems and tabulampot. People have difficulty in marketing vegetable products that are cultivated by urban farming. This service activity aims to form a community in independent aisyiyah branches by utilizing urban farming and digital marketing in the marketing concept. The problem of the community is to utilize land with the concept of urban farming that produces economically so that it can be used as a companion income in filling busyness. The solution of the problem is by providing skills through training in organic plant cultivation in polybags, hydroponic system wick system, verticulture model, and tabulampot. Manufacture of organic and non-organic nutrients as a solution to maintain the availability of fertilizers for plants. Training and practice of making digital marketing with the concept of social media utilizes marketplaces on facebook, whatsapp group, instangram and other platforms.